Synergistic impact of Composite Dietary Antioxidant Index and physical activity on fatty liver disease - Gao, Linxiao; Fang, Haoyu; Zhao, Zhibo; Luo, Wen; Gong, Jianping; Gong, Junhua (Frontiers in Nutrition, 2024)
Background The relationship between dietary antioxidants and fatty liver disease remains a topic of debate. This study aimed to examine the association between the Composite Dietary Antioxidant Index (CDAI) and nonalcoholic fatty liver disease (NAFLD)/metabolic-associated fatty liver disease (MAFLD). Methods The study analyzed data from the 2003–2018 cycles of the National Health and Nutrition Examination Survey. The study included 16,321 individuals aged 20–85 years. Food and nutrient intake data were based on the 24-h recall method. Multivariate logistic regression models were employed to examine the relationship between CDAI and NAFLD/MAFLD. Results In the fully adjusted multivariate logistic regression model, CDAI demonstrated a significant negative correlation with NAFLD and MAFLD. Mediation analysis showed that inflammatory factors partially mediated the relationship between CDAI and NAFLD/MAFLD prevalence. The combination of high CDAI levels with effective physical activity was associated with a greater reduction in NAFLD/MAFLD prevalence than high CDAI levels alone. Conclusion Our study highlighted a negative association between CDAI and NAFLD/MAFLD, mediated by inflammatory factors. Additionally, participants with characteristics of active physical activity and high levels of CDAI were more strongly correlated with the reduced prevalence of NAFLD/MAFLD. Further research in clinical cohorts should be conducted to comprehensively investigate the impact of CDAI on NAFLD/MAFLD prevalence.